Affinity of Tannins to Cellulose: A Chromatographic Tool for Revealing Structure-Activity Patterns - Suominen Essi; Savila Santeri; Sillanpää Mimosa; Damlin Pia; Karonen Maarit (MDPI, 2025)
Food, feed and beverage processing brings tannins into contact with macromolecules, such as proteins and polysaccharides, leading to different chemical and physical interactions. The interactions of tannins with proteins are well known but less is known about the affinity of tannins to polysaccharides. We used bacterial cellulose from nata de coco as a model compound to investigate how tannins and cellulose interact by adsorption measurements using UPLC-DAD. We also explored how the structure of tannins influences these interactions. The model tannins included nine individual structurally different hydrolysable tannins (HTs) and eight well-defined proanthocyanidin (PA) fractions with different monomeric units, mean degree of polymerization and both A- and B-type linkages. Tannins were found to have both strong and weak interactions with bacterial cellulose, depending on the exact structure of the tannin. For HTs, the main structural features affecting the interactions were the structural flexibility of the HT molecule and the number of free galloyl groups. For PAs, prodelphinidins were found to have a higher affinity to cellulose than procyanidins. Similarly to HTs, the presence of free galloyl groups in galloylated PAs and the flexibility of the PA molecule led to a stronger interaction. Adsorption measurements by UPLC-DAD proved to be a sensitive and rapid tool to evaluate the affinity of tannins to cellulose.